The introduction of the bow and arrow in the Argentine Andes (29-34º S): A preliminary metric approximation - Castro, Silvina Celeste (2018)
The study size patterns in projectile points (n=39) from six sites in the Argentine Andes (29-34° S) associated with 17 radiocarbon dates with medians spanning 3080-470 cal. BP. In the northern part of our study area (29° S), one site has domestic llama (Lama glama) bones as early as 5800 cal. BP. In the central and southern part of the study area (32 and 34° S), clear evidence for pastoralism, horticulture, and potentially agriculture is no earlier than 1500 cal. BP. Our study area extends to 34° S, which is the southern limit of pastoral and food-producing societies in South America. In our study area, it is unknown if the bow was adopted early, as in the central Andes, or late and used alongside spears, as in Patagonia. This is the region?s first attempt to metrically distinguish arrows and darts, which is based on shoulder or maximum width, following Shott. The northern sector located at 29° S includes the earliest arrow point, slightly after 3080 cal. BP. This suggests a rapid spread of this technology from the central Andes 16-26° S, where early arrows are dated ~3500-3000 cal. BP. However, at 32 and 34° S, arrows are not clearly present until 1280 cal. BP. For 1280-400 cal. BP (European contact), 96% of points were identified as arrows, suggesting the bow and arrow replaced spear-based weapon systems. A single late dart from 34° S may reflect a late use of this space by hunter-gatherers. The predominance of arrows beginning at 1280 cal. BP is associated with broader changes such as demographic growth, reduced mobility, low-level food production, and herding economies, following similar trends in other regions.